(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The research was conducted with the aim of developing a financial education modules on the subject Savings; to promote household savings in the communal councils, for it was identified how local councils make the promotion of household savings? and described the guidelines for the design of financial education programs. The research was framed within the quantitative paradigm, the design and use descriptive and explanatory research. The research sample, which was intentional, was comprised of 14 community councils registered with the National Institute of Agricultural Research (INIA-Lara). As data collection instrument was a questionnaire response closed, open and mixed. The design of the proposal was developed using the methodology of financial education program for the poor, developed by Microfinance Opportunities, Freedom From Hunger and Citigroup Foundation. The results showed that the DAC-UCLA students, through community service, use the program content of the subjects that are part of the curriculum of study to meet the needs of citizens and community councils surveyed are interested in incorporating activities saving training on the subject.